The Arsenal of Bioactive Molecules in the Skin Secretion of Urodele Amphibians - Barros, Ana L. A. N.; Hamed, Abdelaaty; Marani, Mariela; Moreira, Daniel C.; Eaton, Peter; Plácido, Alexandra; Kato, Massuo J.; Leite, José Roberto S. A. (Frontiers in Pharmacology, 2022)
Urodele amphibians (~768 spp.), salamanders and newts, are a rich source of molecules with bioactive properties, especially those isolated from their skin secretions. These include pharmacological attributes, such as antimicrobial, antioxidant, vasoactive, immune system modulation, and dermal wound healing activities. Considering the high demand for new compounds to guide the discovery of new drugs to treat conventional and novel diseases, this review summarizes the characteristics of molecules identified in the skin of urodele amphibians. We describe urodele-derived peptides and alkaloids, with emphasis on their biological activities, which can be considered new scaffolds for the pharmaceutical industry. Although much more attention has been given to anurans, bioactive molecules produced by urodeles have the potential to be used for biotechnological purposes and stand as viable alternatives for the development of therapeutic agents.